2014
DOI: 10.3109/07420528.2014.993765
|View full text |Cite
|
Sign up to set email alerts
|

Sleep patterns and sleepiness among young students: A longitudinal study before and after admission as trainees and apprentices

Abstract: In developing countries, youngsters start to work during the high school years. Several studies have shown the difficulties associated with double shift, i.e. to work and study concomitantly, and its negative health consequences. Work and study time, as social synchronizers, have significant effects on the sleep-wake cycle (SWC). The purpose of this study was to evaluate sleep patterns and sleepiness in young students before and after entering the workforce as apprentices or trainees. Participants were 40 adol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 38 publications
1
8
0
3
Order By: Relevance
“…(15) The negative impact of the double journey (workstudy) in the sleep of young Brazilian students in the city of São Paulo was confirmed by comparing their sleep rates before the start of the double journey and after engaging with study and work commitments, showing a significant difference between the mean values of sleep time. (16) These findings, together with the results found in the present study are disturbing because sleeping is associated with different modes of memory processing, favoring its consolidation and the recovery of stimuli required at the moment of wakefulness. (17) The lack of sleep may interfere in the process of consolidating students' knowledge and in the quality of trained professionals.…”
Section: Discussionmentioning
confidence: 69%
“…(15) The negative impact of the double journey (workstudy) in the sleep of young Brazilian students in the city of São Paulo was confirmed by comparing their sleep rates before the start of the double journey and after engaging with study and work commitments, showing a significant difference between the mean values of sleep time. (16) These findings, together with the results found in the present study are disturbing because sleeping is associated with different modes of memory processing, favoring its consolidation and the recovery of stimuli required at the moment of wakefulness. (17) The lack of sleep may interfere in the process of consolidating students' knowledge and in the quality of trained professionals.…”
Section: Discussionmentioning
confidence: 69%
“…This difference caused by school and work time is called social jetlag (24). However, it often happens that sleep is not fully recovered, since social incentives such as part-time work and going out with friends push them to sleep still later; sometimes up to > 2 hours the day after the weekend compared to school days (15,25).…”
Section: Acknowledgementsmentioning
confidence: 99%
“…With regard to the binomial sleep deprivation and occupational situation, the tendency is for adolescents from families with less favored socioeconomic conditions to be inserted in the labor market in order to contribute to the household income and maintenance of the family's needs (PINTO et al, 2018). Studies have found that adolescents who work tend to have a poor sleep quality (FISCHER et al, 2014;PINTO et al, 2018), since they feel more tired after having a double shift.…”
Section: Discussionmentioning
confidence: 99%